Delayed elimination communication is a crucial factor in disposable diaper dependence in Chinese preschool-aged children - Yu, Jia-ting; Mao, Qiu-fang; Ji, Feng-ping; Zhao, Ying; Hu, Hui-jie; Zhang, Yan-ping; Yang, Jing; Wang, Qing-wei; Lu, Wei; Wen, Jian Guo (Frontiers in Pediatrics, 2023)
Purpose: Elimination communication (EC) is a milestone in the development of the child. The study aimed to identify potential risk factors for disposable diaper dependence (DDD) and evaluate whether elimination communication can reduce the risk of DDD among children in China. Methods: A randomized cross-sectional study was performed on 13,500 children in mainland China from October 2019 to March 2020. An anonymous questionnaire was used to collect information including the sociodemographic characteristics, details about DDD and EC, and the effect of DDD on the quality of life of children. Data were analyzed by SPSS and R software. Results: The overall prevalence of DDD was 4.17% (4.31% in boys; 4.02% in girls) and decreased with age, from 8.71% at 2 years to 0.73% at 6 years (χ2trend=210.392, P<0.001). Four independent factors - age, location, education level of the caregiver and EC - were identified to be significantly associated with DDD risk. EC failure was a crucial risk factor for DDD in children (P<0.001). Compared with EC onset after 12 months of age, EC onset before 12 months of age was associated with a 79.6% (model 2) reduction in DDD. Four variables were selected to establish the nomogram for DDD. The C-index (0.770) and the AUC (> 0.7) indicated satisfactory discriminative ability of the nomogram. The calibration diagrams showed favorable consistency between the prediction of the nomogram and actual observations. Conclusions: Delayed EC is a crucial risk factor for DDD. Timely cessation of the use of disposable diapers (DDs) and early EC help to reduce the risk of DDD in children. It is necessary to construct a DDD diagnostic nomogram to assist clinicians in making scientific clinical decisions.